2022
DOI: 10.3389/fmicb.2022.822243
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Biofilm Formation by Streptococcus pyogenes emm 1 Isolated From Patients With Necrotizing Soft Tissue Infections

Abstract: ObjectivesBiofilm formation has been demonstrated in muscle and soft tissue samples from patients with necrotizing soft tissue infection (NSTI) caused by Streptococcus pyogenes, but the clinical importance of this observation is not clear. Although M-protein has been shown to be important for in vitro biofilm formation in S. pyogenes, the evidence for an association between emm type and biofilm forming capacity is conflicting. Here we characterize the biofilm forming capacity in a collection of S. pyogenes iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…S. pyogenes is able to form biofilms which have been associated with diseases such as tonsilitis and cellulitis [ 37 ]. Recently, it was shown that S. pyogenes serotype M1 strains consistently formed biofilms in patients with necrotising fasciitis (‘flesh-eating disease’) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…S. pyogenes is able to form biofilms which have been associated with diseases such as tonsilitis and cellulitis [ 37 ]. Recently, it was shown that S. pyogenes serotype M1 strains consistently formed biofilms in patients with necrotising fasciitis (‘flesh-eating disease’) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…167008, Denmark), covered with a lid, and incubated at 37°C under aerobic conditions for 24 h or 48 h (for slower growing strains). The procedure for measuring the biofilm-forming capacity was performed according to Skutlaberg et al ( 15 ) with heat fixing and staining with crystal violet. A BioTek PowerWave XS microplate reader (BioTek, Winooski, VT, United States) was used for the OD600 measurements.…”
Section: Methodsmentioning
confidence: 99%